AVRUPA BİRLİĞİ HUKUKU UYARINCA MARKANIN "GERÇEK KULLANIM" PROBLEMİ - (:unkn) unknown (My University, 2016)
Fikri Mülkiyete dair uluslararası ilgi günümüzde oldukça dikkat çekicidir. Fikri haklara dair bu ilgi dürüst ticaretin teşviki ve ekonomik kalkınma ile de tamamen bağlantılıdır ancak serbest ticaretin faydaları sadece fikri mülkiyet haklarının kabul edilmesiyle ilgili bulunmamaktadır. Avrupa Birliği'nin İşleyişi Hakkında Anlaşma olan ve günümüzde Lizbon Anlaşması olarak adlandırılan Roma Anlaşması'nın belirgin ekonomik başarıları, Kuzey Amerika Serbest Ticaret Anlaşması ve Gümrük Tarifeleri ve Ticaret Genel Anlaşması olarak bilinen Uruguay Raundu, Ticaretle Bağlantılı Fikri Mülkiyet Hakları Anlaşması ile birlikte; Dünya Ticaret Örgütü, ekonomik büyü- menin desteklenmesi için hükümetlere Fikri Mülkiyet haklarının uyumlaştırılması baskısı uygulamaktadır. Tüm dünyada birbirleri ile uyumlaştırılan hukuki mevzuat gelişirken, bölgesel gruplar da özellikli olarak Fikri Mülkiyet korunmasının oluşumuna odaklanmaktadırlar. Avrupa'da ulusal ve Birlik dü- zeyinde kombine olan marka içtihat hukuku politik ve stratejik bir temele dayanmaktadır. Avrupa'nın küresel rekabet edebilirlikteki yükselişine dair endişeler marka hukuku korumasını önceye nazaran daha önemli kılmaktadır. "Gerçek Kullanım" konusuna dair sürüncemeli görüşmeler günümüzde Birliğin en mühim yasal güçlüklerinden birini oluşturmaktadır. Bu çalışma markanın kullanımıyla ilgili üç temel mevzuya dayanmaktadır; giriş bölümünde markanın gerçek kullanım gerekliliği, ikinci bölümde ABAD içti- hatları uyarınca Birlik Markasının bölgesel kullanımı ve getirilen yorumlar, son bölümde ise "gerçek kulla- nım" kavramı dava hukuku yoluyla incelenmiştir.

The international interest in intellectual property is quite remarkable today and now completely linked to promotion of fair trade and economic development, but it is the economic benefits of free trade not the embrace of intellectual property rights per se which evolves the harmonization process. The apparent economic successes of the Treaty of Rome now the Lisbon Treaty on the Functioning of the European Union, the North American Free Trade Agreement and Uruguay Round of the General Agreement on Tariffs and Trade, including the Agreement on TradeRelated aspects of Intellectual Property rights, that resulted in the World Trade Organization have caused governments to continue pressing for harmonized IP protection in support of economic growth.While improving harmonized and co-existing legislations all over the world there are also territorial grouping that focus on establishing specific kinds of IP protection. The combination of national and Unionwide the trademark case law in Europe is as a political and strategic basis. This together with increasing concerns about Europe's global competitiveness makes the trademark protection even more circumstantial than before. The protracted negotiations on the 'genuine use' concept regarding the trademark protection constituted one of the major legal challenges of the (at the time) Community. This study focuses primarily on the three main issues on use of trademarks: In the introductory part, the concept of the genuine use requirements is explained by examining trademark use. Secondly, the territorial use of the Community Trade Mark Regulation is analysed in the light interpretation of the Court of Justice of the European Union. The last part of the study is mainly focused on case law related to the '-genuine use-' concept.
'GENUINE USE' OF TRADEMARK PROBLEMATIQUE IN THE COURSE OF EUROPEAN UNION LAW
Keywords: Uluslararası İlişkiler